Wind Generation Impact on Symmetrical Fault Level at Grid Buses - A. Hamzeh; Sadeq A. Hamed; Zakaria Al-Omari (Institute of Advanced Engineering and Science, 2018)
This paper mainly aims at evaluating quantitatively the impact of wind turbine generators (WTGs) on fault level (FL) in case of a balanced fault occurring in the host grid (HG). This impact is not generic but it depends on the grid configuration, operation mode, and load profile; the impact may be positive for a network while it is negative for another one. Therefore, the impact will be estimated for a specific distribution network (DN). The grid faults and wind generations (WGs) are simulated by the simulation tool Power Factory DigSilent 14.0.506. The paper addresses the influence on FL of grid buses in general and particularly on FL of the point of common coupling (PCC). The effect of both penetration and dispersion levels of embedded WTGs on fault response is also investigated. Moreover, the influence of WG type on FL is assessed. It is concluded, among other points, that the FL at PCC could rise by about 150% and 17% due to embedded WG of type 1 and type 2 respectively, what it leads to the recommendation to avoid installing type 1 wind systems for new wind farms